Umbral Calculus and the Frobenius-Euler Polynomials - Dae San Kim; Taekyun Kim; Sang-Hun Lee (Abstract and Applied Analysis)
We study some properties of umbral calculus related to the Appell sequence. From those properties, we derive new and interesting identities of the Frobenius-Euler polynomials.